Developing a Hernia Mesh Tissue Integration Index Using a Porcine Model—A Pilot Study - Patiniott, Paul; Stagg, Brendan; Karatassas, Alex; Maddern, Guy (Frontiers in Surgery, 2020)
Introduction: With so many prosthetics available, it can be difficult for surgeons to choose the most appropriate hernia mesh. Successful hernia repair mandates an understanding of how the patient’s inflammatory response influences surgical outcomes. Failure to appreciate the importance of the biological aspect of hernia repair can be very costly as emerging evidence supports that biofilm formation and reduction in effective mesh porosity gives rise to long-term mesh complications including fibrosis, chronic mesh infection, and pain. In this pilot study, we utilized a large animal (porcine) model to develop a numerical Mesh Tissue Integration (MTI) Index focused on visible tissue ingrowth, fibrosis, adhesion formation and resorption of mesh. The aim is to help surgeons adopt an evidence-based approach in selecting the most appropriate mesh according to its tissue ingrowth characteristics, matched to the patient to achieve improved surgical outcomes and optimal patient-centered care. Methods: Two 40kg female Landrace pigs were recruited for this pilot study. A total of eight commonly used hernia mesh products and two controls measuring 5cm x 5cm were surgically implanted in subrectus and intraperitoneal planes. The pigs were euthanised at 2 weeks and 4 weeks respectively. The abdominal wall was explanted, and the mesh specimens underwent macroscopic, histologic and biomechanical analysis, with engineering and pathology teams blinded to the mesh. Results: Significant differences between the degrees of MTI were observed at 2 weeks and the distinctions were even more apparent at 4 weeks. One of the interesting incidental findings we observed is that mesh products placed in the subrectus plane displayed greater degrees of adhesion strength and integration than those placed intraperitoneally. Conclusion: This pilot study is one of the first to propose a functional, biological standardised model for comparing hernia mesh products. The results are encouraging and demonstrate that this is a robust and transferrable model for assessing MTI in hernia mesh. The intention for this model is that it will be utilised synergistically with long term mesh/patient outcome registries and databases to inform improved matching of mesh to patient, particularly in the setting of the complex hernia repair and abdominal wall reconstruction.